Conceptualizing Blockchain in The Music Industry - Mahmoud Mohamed, Moustafa (My University, 2020)
As blockchain technology continues to evoke interest and engagement across companies, organizations, industries, and governments, the desire to integrate the technology is evident. The discussion around blockchain often implies promises of decentralization, transparency, and disruption. The music industry specifically has been noted to potentially gain from the implementation of blockchain, making it a great context for exploration: the industry is constructed of multiple stakeholders with complicated and often dysfunctional connections. This research aims to understand how blockchain is utilized in the context of music industry. It distinctively tries to understand the technical structure of the applied blockchain, the implications to business logic and structures, and lastly the long-term intersection of blockchain and the music industry. This research was conducted as a qualitative multiple-case study. With an inductive and intensive approach, the objective was to explore the use of blockchain in a holistic nature from the perspective of each case. The empirical data was collected from secondary whitepapers published by each case company. Each whitepaper detailed the technical and the business structure as it pertains to blockchain. The data revealed how blockchain governs engagement and the positioning of each stake-holder in the ecosystem and in relation to each other in the presence, or lack thereof, of blockchain. It was concluded that blockchain can be utilized in varying ways and to varying degrees. The consequential effects can be observed in the governance, structure, and business logic of each case, which this research showcases in detail. While this research was able to provide differing possibilities for use, it could not provide evidence of blockchain being mature enough for mass adoption, supporting arguments presented in previous research and theory.

Blockchain-teknologian noustessa yhä tunnetummaksi, monen yrityksen ja tahon tavoitteena on tutkia tämän teknologian hyödyntämistä. Musiikkiteollisuus on erityisesti mainittu sopivan kyseiseen integroimiseen: musiikkiteollisuudessa on monia sidosryhmiä, joiden välillä on monimutkaisia ja usein ongelmallisia suhteita. Tämän tutkimuksen tavoitteena on ymmärtää blockchain-teknologian käyttö musiikkiteollisuudessa. Ymmärrys ulottuu tekniseen hyödyntämiseen, liiketoiminnallisiin seuraamuksiin ja musiikkiteollisuuden ja teknologian pitkäaikaiseen risteytymään. Tutkimus suoritettiin laadullisena monitapaustutkimuksena, jonka tarkoituksena oli kerätä kokonaisvaltainen ymmärrys blockchain-teknologian käytöstä jokaisen tapauksen näkökulmasta. Empiirinen data kerättiin sekundääriaineistosta, josta tuli ilmi jokaisen tapauksen tekninen ja liiketoiminnallinen malli. Aineistoa lähestyttiin induktiivisesti ja analysoitiin intensiivisesti. Tulokset paljastivat kuinka blockchain-teknologia ohjasi kanssakäymistä ja miten eri sidosryhmät asennoituivat teknologiaan ja toisiinsa nähden. Teknologiaa hyödynnettiin eri tavoilla ja eri laajuudella. Teknologian seurauksena jokaisessa tapauksessa ilmestyi huomattavia eroja tapausten hallinnoinnissa, rakenteissa ja liiketoiminnan logiikassa. Tämä tutkimus erittelee tarkasti jokaisen tapauksen tekniset yksityiskohdat ja niistä seuraavat edellä mainitut erot. Johtopäätöksenä kuitenkin todetaan, että tutkimuksessa esiintyvät tapaukset ovat vielä kehittymisvaiheessa, eivätkä voi näin puoltaa teknologian olevan valmiina täysmittaiseen adoptioon. Tämä osaltaan tukee teoriassa esiin tuotuja väitteitä teknologian epäkypsyydestä.
Keywords: Blockchain, music industry, tokenization, token economic model, DAO